Comparative Analysis of E-commerce, E-wallet and Friend Environment on Student Consumptive Behavior: Analisis Perbandingan E-commerce, E-wallet dan Lingkungan Teman Terhadap Perilaku Konsumtif Mahasiswa - Munawaroh, Wahidatul; Abidin, Fityan Izza Noor (Indonesian Journal of Law and Economics Review, 2024)
General Background: The rise of technology has made online shopping convenient for university students, but this can lead to prioritizing wants over needs, resulting in excessive consumer behavior. Specific Background: This study examines the influence of e-commerce convenience, e-wallet promotions, and peer environments on the consumptive behavior of accounting and management students at Universitas Muhammadiyah Sidoarjo, addressing conflicting findings in previous research. Knowledge Gap: Previous studies yield inconsistent results regarding the impact of e-commerce ease on consumptive behavior and lack comprehensive analysis on e-wallet promotions and peer influence. Aims: The research aims to evaluate how these variables affect consumptive behavior and to identify differences between accounting and management students. Results: Findings indicate that e-commerce convenience does not affect accounting students but does influence management students. E-wallet promotions and peer environments significantly impact both groups, with notable differences in their effects. Novelty: This study enhances understanding of consumer behavior among Indonesian university students by emphasizing the varying impacts of technological and social factors. Implications: Insights from this research can guide e-commerce platforms and e-wallet providers in crafting targeted strategies that promote responsible consumerism among students. Highlights: E-commerce convenience significantly affects management students' consumptive behavior but not accounting students. E-wallet promotions and peer environments positively influence consumptive behavior in both student groups. The study highlights differences in the impact of promotional strategies and peer dynamics on students' shopping habits. Keywords: Ease of E-Commerce, E-Wallet Promotions, Peer Influence, Consumptive Behavior, Friend Environment